Vaccine Refusal: A Preliminary Interdisciplinary Investigation - Brakel, Linda A. W.; Foxall, Gordon R. (Frontiers in Public Health, 2022)
Many people who generally receive standard recommended inoculations refuse to partake of COVID-19 vaccines, preventatives that are effective, safe, and life-saving amidst the current pandemic. Our quest is to understand this puzzling and dangerous phenomenon, as it exists among US and UK citizens, whom in other respects would be regarded as quite regular. We will discuss Vaccine Refusal compared with two better understood phenomena: addiction, and akrasia, along with the related matters of human action, intention, agency, will, and identity. Vaccine Refusal, we will argue, appears to be rewarded by “informational reinforcement” leading to heightened arousal, along with increases in self-esteem resulting from “bucking the trend,” asserting one's “superior” understanding, and “tribal identity” in acting against social norms. These factors provide an overall reward amounting to satisfaction that outweighs the well-known consequences of COVID-19 infections. Our investigations will also lead us to a pair of epistemological hypotheses about two subtypes of the Vaccine Refusers under consideration here.